Surveillance and diagnostics dataset on Sri Lankan cassava mosaic virus (Fam. Geminiviridae) and CMD in Thailand - Siriwan, Wanwisa; Jiménez Polo, Jenyfer; Hemniam, Nuannapa; Saokham, Kingkan; Cuéllar, Wilmer Jose (International Center for Tropical Agriculture, 2020)
Emergent agricultural pathogens cause severe damage worldwide. Standard surveillance and diagnostic protocols need to be evaluated and implemented at regional level, particularly with diseases caused by a wide range of pathogens that can induce similar symptoms. This dataset provides a description of surveillance and diagnostics data for CMD in Thailand (2019), indicating location of the surveyed fields, presence of visual symptoms, symptom severity and PCR-diagnostic results with two primer sets, both of them targeting the CP region. All samples were collected using a standard protocol as described in the associated manuscript. More information is available upon request.